2022
DOI: 10.1002/jlb.3ma0322-171r
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β/NF-κB signaling inhibits IGF-1 production via let-7f-5p in dendritic epidermal T cells

Abstract: Dendritic epidermal T cells (DETCs) are the main source of insulin‐like growth factor‐1 (IGF‐1) in epidermal tissue, which promote re‐epithelialization and wound healing. In refractory wounds, IL‐1β has been shown to activate NF‐κB and suppress IGF‐1 expression in DETCs. Nevertheless, the underlying mechanisms remain unclear. In this study, chromatin immunoprecipitation analysis revealed that IL‐1β did not inhibit NF‐κB binding to IGF‐1 promoter, indicating that IL‐1β/NF‐κB may suppress IGF‐1 expression by alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These increases in local synthesis of pro-inflammatory cytokines may significantly influence the secretion of IGF1. It was found that IL1B inhibits IGF1 production in dendritic epidermal T cells (Li et al, 2022). Previous studies also demonstrated that IL6 inhibits the secretion of IGF1 and that IL6 overproduction is a mechanism implicated in IGF1 downregulation (Barbieri et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…These increases in local synthesis of pro-inflammatory cytokines may significantly influence the secretion of IGF1. It was found that IL1B inhibits IGF1 production in dendritic epidermal T cells (Li et al, 2022). Previous studies also demonstrated that IL6 inhibits the secretion of IGF1 and that IL6 overproduction is a mechanism implicated in IGF1 downregulation (Barbieri et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…It was widely known that NF-ĸB plays a role upstream of NLRP3 (34). Whereas, over-expressed NLRP3 also contributes to the expression of IL-1β and IL-18, and many studies showed that IL-1β can stimulate the activation of NF-ĸB signalling pathway through a feedback loop (35)(36)(37)(38). The up-regulated IL-1β production might lead to the lung injury.…”
Section: Discussionmentioning
confidence: 99%